Methodologies for the calculation of greenhouse gas emissions: description of the control project in a cement-producing Industry - Martínez-Rodríguez, María Concepción (2021)
The global cement industry is responsible for approximately 5% of total CO2 emissions in the world, as a result of chemical reactions in clinker production, fuel consumption, electricity use, transportation of raw materials and finished products. The general objective of this research is to provide the methodological bases for the preparation of the emission control project with a view to an initial audit for Greenhouse Gases (GHG) in a Cement industry in order to identify the management level of its systems and processes for calculating GHG scope 1 and 2 and suggest a GHG calculation procedure that strengthens the GHG emissions reporting processes. This work was based on the ISO 14064-2, regarding the Specification, at the project level, for the quantification, monitoring and the basis for defining the report of the reduction of emissions or the increase in greenhouse gas removals. The main variables to consider in the validation of the inventory of GHG emissions that are suggested will be considered in the framework of the audit taking first level; to set within the company the initial year or zero, and to integrate a historical compendium of at least 5 years of GHG emissions, to estimate emissions from calcination of raw material, by use of fuels and cement production.